Uma proposta de ensino de astronomia para o Ensino Médio a partir de uma breve história da evolução de nosso conhecimento sobre o universo - Rogério, Túlio Permino (2017)
The inclusion of Astronomy topics in Basic Education is supported by several laws in force and is already well justified in the literature of the area of teaching of Physics and Astronomy, however it is not common practice in classrooms for several reasons. In order to disseminate this theme, in secondary schools and also in academic research in Teaching, this proposal seeks to investigate the possible contributions that the application of the dynamics of the Three Pedagogical Moments can promote in the Teaching of Astronomy in a public school in the state of Holy Spirit. This dynamic has a dialogic and problematizing perspective. The dynamics consists of an Initial Problematization, which seeks to awaken in the student the need to acquire knowledge, followed by a moment of Knowledge Organization, when the necessary knowledge for the understanding of the subject is studied, ending in an Application of Knowledge, which is a moment of using organized knowledge to arrive at a synthesis about the phenomenon studied, or extrapolating to new situations, whose understanding also applies the knowledge previously studied. With this approach, the expectation was to achieve greater participation of the students, since there was room for them to bring their doubts and expectations about Astronomy to the classroom and, with this, they could participate more actively during the teaching-learning process, avoiding a mere direct transmission of information, without respecting their experiences and knowledge. The general structure of the proposal counts on six blocks of activities: the students’ previous conceptions; observations of the night sky; geocentric and heliocentric solar system; distances between galaxies; astronomical proportions and distances; and evaluation of the proposal. The data were collected from questionnaires, written activities, logbooks and recorded audios, with consent. During the classes, analyzing the applied activities and the interviews, it was evidenced a good involvement of the students who seem to have appropriated the discussions and activities carried out. The observation of students’ postures allowed the evaluation of characteristics of their autonomy profile, and the results indicate some characteristics of more reflective students. Although we recognize the limitations of this proposal, it seems to have great potential for interventions in introductory astronomy studies that seek to work beyond the knowledge present in didactic materials, promoting a constant dialogue between astronomical knowledge and aspects that can be experienced in daily life.